2021
DOI: 10.1680/jstbu.20.00110
|View full text |Cite
|
Sign up to set email alerts
|

Fire safety engineering principles applied to a multi-storey steel building

Abstract: In this paper, fire safety engineering principles were applied to a steel-framed office building. The case study consisted of a 15-storey steel moment-resisting frame designed in Japan. Once the performance criteria had been defined, two severe fire scenarios for the unprotected structure, implying a different degree of building collapse, were identified and modelled in zone models, OZone and consolidated fire and smoke transport (CFast), as well as in the computational fluid dynamics software Fire Dynamics Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…And what's more, fire behaviour of multi‐storey buildings typically assumes good compartmentalization between floors; this also applies to steel frames designed in highly seismic regions. [ 46 ] To minimise the potential spread of fire among the floors which may cause severe damage and be critical to structural stability, at the very least, the fire compartmentalization of a building equipped with DRBeS should be carefully analysed because of the cut through the slab.…”
Section: Discussionmentioning
confidence: 99%
“…And what's more, fire behaviour of multi‐storey buildings typically assumes good compartmentalization between floors; this also applies to steel frames designed in highly seismic regions. [ 46 ] To minimise the potential spread of fire among the floors which may cause severe damage and be critical to structural stability, at the very least, the fire compartmentalization of a building equipped with DRBeS should be carefully analysed because of the cut through the slab.…”
Section: Discussionmentioning
confidence: 99%
“…A reasonable mesh size is the premise to ensure the reliability of the simulation results, so mesh independence analysis is needed [36][37][38]. According to the calculation, the mesh size should be selected in the range of 0.0889 to 0.3556.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Buckling curves for T sections obtained from half H or I section (L, T and X made of coupled leg sections can be found in Possidente et al (2020)). S235, S275 and S355 steel grade…”
Section: Figurementioning
confidence: 99%
“…Hence, the spread of a fire may have significant consequences. In terms of fire risk, for instance Possidente et al (2020) showed an example of application of fire risk assessment applied to a multi-storey steel building.…”
Section: Introductionmentioning
confidence: 99%